2013
DOI: 10.1063/1.4818544
|View full text |Cite
|
Sign up to set email alerts
|

Eigenvector centrality of nodes in multiplex networks

Abstract: We extend the concept of eigenvector centrality to multiplex networks, and introduce several alternative parameters that quantify the importance of nodes in a multi-layered networked system, including the definition of vectorial-type centralities. In addition, we rigorously show that, under reasonable conditions, such centrality measures exist and are unique. Computer experiments and simulations demonstrate that the proposed measures provide substantially different results when applied to the same multiplex st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
188
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 245 publications
(192 citation statements)
references
References 30 publications
1
188
0
Order By: Relevance
“…Finally also the community structure of networks in different layer might be correlated, with communities defined in different layers overlapping with each other. Inference problems on multiplex networks, including the determination of centrality measures for nodes [31][32][33] and the characterization of the multiplex network mesoscale structure 29,30,[35][36][37][38] , can take advantage of these correlations to extract more information from these datasets. In this way a clear path is defined for extracting relevant information from multiplex network structures, which cannot be unveiled by analyzing its single layers taken in isolation or its aggregated description.…”
Section: Structural Multiplex Measures a Multiplex Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally also the community structure of networks in different layer might be correlated, with communities defined in different layers overlapping with each other. Inference problems on multiplex networks, including the determination of centrality measures for nodes [31][32][33] and the characterization of the multiplex network mesoscale structure 29,30,[35][36][37][38] , can take advantage of these correlations to extract more information from these datasets. In this way a clear path is defined for extracting relevant information from multiplex network structures, which cannot be unveiled by analyzing its single layers taken in isolation or its aggregated description.…”
Section: Structural Multiplex Measures a Multiplex Networkmentioning
confidence: 99%
“…Quantifying the centrality of the nodes in multiplex networks is a fundamental problem that in these last years has attracted increasing attention from the network science community [31][32][33] . Among the different proposed centrality measures, the Multiplex PageRank 32 can be used to assess how the centrality of a node in a single layer is affected by the centrality of the same node in another layer.…”
mentioning
confidence: 99%
“…Similarly, in biological systems basic constituents such as proteins can have physical, co-localization, genetic or many other types of interactions. Recently, it has been shown that retaining such multi-dimensional information 7 and modelling the structure of interdependent and multilayer systems respectively through interdependent 8 and multilayer networks [9][10][11][12] reveals new nontrivial structural properties [13][14][15][16][17][18][19][20] and relevant emergent physical phenomena [21][22][23][24][25][26][27] .…”
mentioning
confidence: 99%
“…New multiplex datasets [9][10][11][12][13][14] and multiplex network measures have been introduced in order to quantify their complexity. Examples of such measures are the overlap [11,13,14] of the links in different layers, the interdependence [12,15] that extends the concept of betweenness centrality to multiplexes, or the centrality measures [16,17]. Many dynamical processes have been defined on multiplexes, including cascades of failure in interdependent networks [18][19][20][21][22], antagonistic percolation [23], dynamical cascades [24], diffusion [25], epidemic spreading [26], election models [27], game theory [28,29], etc.…”
Section: Introductionmentioning
confidence: 99%